The effect of zirconium on the strength cold-deformed reinforcement properties - E. S. Eltsova; O. Yu. Khodosovskaya; Yu. I. Kozyreva (Литьë и металлургия)
The possibility of using zirconium in the steel composition of the Arx-Zr brand in the cold-deformed reinforcement of a threesided periodic profile of strength class 500 MPa manufacture in order to increase the finished reinforcement strength characteristics is determined. There is test results information of a wire rod /blank with an 8.8 mm diameter, which is intended for the manufacture of cold-deformed fittings with an 8.0 mm diameter, are presented. A comparative analysis of the physical and mechanical finished cold-deformed fittings properties with an 8.0 mm diameter made of steel grade Arch-Zr and fittings of a three-sided periodic profile made of wire rod of ordinary quality was done. Analyzed the obtained properties and the cold-deformed fittings evaluation for meeting the standards’ requirements. Identified that the addition of zirconium to steel in an amount of 0.019 % does not affect the final strength characteristics of the produced cold-deformed reinforcement of a three-sided periodic profile of strength class 500 MPa. The values of the physical and mechanical parameters of the produced cold-deformed reinforcement are similar to the cold-formed reinforcement parameters made of wire rod of ordinary quality without the use of alloying.